Media, linguaggi, comunicazione: scenari del presente e del futuro - Gola, Elisabetta; Volterrani, Andrea; Meloni, Fabrizio; Careddu, Arianna (RESOCONTI, 2023)
This volume represents an account of the conference "Media, languages, communication: scenarios of the present and the future," which took place in Cagliari, Italy, on October 13 and 14, 2022. The conference was jointly organized by the University of Cagliari, the Cagliari Hospital-University Hospital, and the University of Rome "Tor Vergata," with the intention of bringing together academics and professionals, philosophers, sociologists, linguists, as well as journalists, graphic designers, and game designers, to discuss some key issues in the landscape on communication scenarios. Each chapter of the text focuses on one of the issues addressed in the panels, with some additions necessary to make the volume usable. Overall, the importance of relationship, languages and media with respect to the effects of communication in social, educational, public and cultural communication is shown.